Fundraising management : - Sargeant, Adrian. (Routledge, 2009)
‘An invaluable core text for all practising fundraisers, but simply a ‘must read’ for those studying for the Institute of Fundraising Certificate in Fundraising Management. This latest edition is packed full of state of the art best practice, backed by case studies and underpinned by the academic rigour you would expect from Sargeant and Jay.’